Establishment of local diagnostic reference level (LDRLS) for digital mobile radiography in neonate population - Nazar, Nur Athirah Syuhada (Universiti Sains Malaysia, 2024)
Introduction: Radiology techniques such as chest AP, abdomen AP, and chestabdomen X-rays are frequently performed on neonates to address various clinical conditions. However, a comprehensive Diagnostic Reference Level (DRL) that considers the specific needs and categories of neonates is currently lacking. Developing such DRLs is crucial for optimising radiation doses and ensuring safe imaging practises tailored to the delicate physiology of neonates. Objectives: This study aims to evaluate the dose distribution (Air Kerma-Area Product, PKA in mGy.cm2) for chest, abdomen, and chest-abdomen AP studies for mobile digital X-ray units among neonates and establish the local diagnostic reference levels (LDRLs) for these studies specifically for neonates. Method: In this study, a retrospective survey of X-ray data was conducted on 694 neonate samples, aged 1 to 28 days, who underwent chest AP, abdomen AP, or chest-abdomen X-ray examinations between January 2022 and December 2023 at Hospital Universiti Sains Malaysia (HUSM) using a mobile Samsung GM85 unit. The dose distributions (PKA in mGy.cm2) were evaluated, and the local diagnostic reference levels were established for these selected studies. Results: The dose distribution (PKA in mGy.cm2) revealed the highest DRL (Q3) value in the abdomen AP (17.26 mGy.cm2) and the lowest in the chest AP (6.79 mGy.cm2). The reference range of PKA for the selected X-ray examinations are abdomen AP (1.98 – 140.98 mGy.cm2), chest-abdomen (2.62 – 132.66 mGy.cm2), and chest AP (0.97 – 24.50 mGy.cm2). Conclusion: The findings of this study reveal that KAP value proportionally increases with kV, mAs and FOV. The DRL for neonates varies depending on the area being scanned for each X-ray radiography examination. In summary, this study makes a significant contribution to enhancing radiation safety, patient care, and clinical decision-making in neonatal X-ray radiography. Generally, this study agrees with other conducted DRL studies.